2010
DOI: 10.1080/10402001003728889
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Dimple Parameters on the Friction of Sliding Surfaces Investigated by Orthogonal Experiments

Abstract: Surface texturing has proven to be an effective method to improve tribological performance of sliding surfaces. The pattern of microdimples is the most popular surface texture because it is supposed to obtain additional hydrodynamic pressure easily.In order to evaluate the significance of the dimple parameters, including dimple diameter, depth, and area ratio, to the frictional performance, the dimple patterns with dimple diameter from 50 to 300 µm, dimple depth from 5 to 20 µm, and area ratio from 5 to 20% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
85
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 24 publications
6
85
0
Order By: Relevance
“…In a tribological study on piston ring/cylinder liner contact, Rahmani et al [4] investigated and optimised negative and positive type texture with different shapes in hydrodynamic lubrication. They concluded that the increase of textures on the bearing surface is beneficial and reiterated the similar observations of Yan et al [3].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…In a tribological study on piston ring/cylinder liner contact, Rahmani et al [4] investigated and optimised negative and positive type texture with different shapes in hydrodynamic lubrication. They concluded that the increase of textures on the bearing surface is beneficial and reiterated the similar observations of Yan et al [3].…”
Section: Introductionsupporting
confidence: 67%
“…In this regard, ddifferent researchers reported different optimum texture geometries, indicating that there are still some gaps in understanding the effect of surface texturing. For instance, Yan et al [3] suggested that the dimple area density was the most important geometrical parameter, followed by the dimple depth and the dimple diameter. In a tribological study on piston ring/cylinder liner contact, Rahmani et al [4] investigated and optimised negative and positive type texture with different shapes in hydrodynamic lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…For the tribo-pairs of metals lubricated by oil, several studies under controlled laboratory conditions have been performed in order to analyze the effect of area density of dimples on the coefficient of friction. Several experimental works show that the area density of dimples in the range of 5-13% is preferable for friction reduction, and the area density of dimples of above 20 % usually causes increasing the friction coefficient value [17,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Dimple diameter, depth, and area density of dimples are the three major parameters of evenly distributed dimple patterns [17][18][19]. By considering all the geometric parameters, texture shapes are optimized to achieve the optimum shapes which will provide the best tribological performance in terms of minimum friction and maximum load carrying capacity [3].…”
Section: Introductionmentioning
confidence: 99%
“…The wear behaviour of wrought aluminum alloys has received substantial attention and attractive alternatives to ferrous materials for tribological applications due to their high thermal conductivity and low density. However, their uses have been limited by their inferior strength, rigidity and wear resistance [3,4] . In general, several factors affect the wear equations, such as operational parameters, topography of the surface contact, geometry, speed, load, and coefficient of sliding friction.…”
Section: Introductionmentioning
confidence: 99%